Where is the love? Developing loving relationships as an essential component of professional infant care. Issue 2 (3rd April 2018) - Recchia, Susan L.; Shin, Minsun; Snaider, Carolina
ABSTRACT: Using a grounded theory approach, this study explores the ways a diverse group of pre-service student caregivers, new to teaching and caring for infants, come to understand notions of 'love' during an infant practicum course in the United States. Through analysing weekly dialogue journals and course assignments produced by each of the 8 participants, we captured their unique and complex experiences of love and care in the infant room. Results revealed that for love and trust between student caregivers and babies to evolve, caregivers need to acknowledge babies as unique individuals, and commit to getting to know and understand them in depth. Further, student caregivers develop intimate caregiving connections and loving relationships with babies through shared time and space. Loving care for babies became an integral experience and an essential pedagogical tool for student caregivers as they developed their professional identities. Our exploration of the deep and complex connections between love, care, and education in childcare, which have been for the most part overlooked, silenced, or simply ignored, has important implications for re-envisioning the notion of love in non-familial infant care.